The Appearance of Pluractionality in Turkish Sign Language: A Corpus-based examination and Classification - Yasemin GÜÇLÜTÜRK; İclal ERGENÇ (Dilbilim Araştırmaları Dergisi)
Pluractionality is a grammatical category that is formed by encoding information such as plurality and distribution in the semantic dimension with the use of reduplication markers. The pluractionality markers encode person, number, place and time distributions in the semantic dimension of the word. Although there is a trend towards pluractionality in current studies, there is no extensive classification on pluractionality. In this study, a classification on TİD pluractionality is presented by portraying structural and functional findings obtained from the corpus-based examination on pluractionality in TİD. Observing the structure of pluractionality in TİD there are many independent, non-manual and combinatory pluractional markers, in TİD. The independent type consists of /-REP/, /-ARC/, /-PC/ and /-2HND/ pluractional markers. The non-manual type includes /-PC/ and /-BS/ pluractional markers. As for the combinatory type which consists of at least two markers, it consists of /-REP + ARC/, /-REP + 2HND/, /-ARC + 2HND/, /-REP + BS/, /-REP + PC/, /-ALT + PC/, /-ALT + BS/, /-ARC + BS/ and /-ARC + PC/ pluractional markers. On a functional level, the semantic behaviours were examined in terms of the semantic classification put forward by Kuhn and Aristodemo (2017), TİD pluractional markers enable all three types, the marker can enable the readings (a) and (b), (b and (c), or all three readings. Compared with pluractional structures in other sign languages, non-manual pluractional markers in TİD are as effective as manual pluractional markers.